2014
DOI: 10.1080/02687038.2014.913769
|View full text |Cite
|
Sign up to set email alerts
|

What matters in semantic feature processing for persons with stroke-aphasia: Evidence from an auditory concept–feature verification task

Abstract: Background The relationship between object concept domains (living vs. nonliving) and their underlying feature structures is a frequent area of investigation regarding semantic processing in healthy individuals and some individuals with neuropsychological impairment resulting from herpes simplex encephalitis, semantic dementia and Alzheimer's disease. However, this relationship has been less well-investigated in persons with stroke-aphasia (PWA), even though many treatments for anomia following stroke are pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…For PWA, we observed a role for the provision of distinctive features for adequate description of objects, a feature type that may be particularly difficult to access for some individuals with aphasia (e.g., Mason-Baughman & Wallace, 2014). In addition, it may be that we need to examine these relationships from a more finely grained perspective, both with respect to more discrete feature typeconcept relationships (e.g., fruit: visual-perceptual color, animal: visual-perceptual form) and across performance of persons with aphasia with different lesion profiles (e.g., Gainotti, 2006; see also Antonucci, 2014aAntonucci, , 2014b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For PWA, we observed a role for the provision of distinctive features for adequate description of objects, a feature type that may be particularly difficult to access for some individuals with aphasia (e.g., Mason-Baughman & Wallace, 2014). In addition, it may be that we need to examine these relationships from a more finely grained perspective, both with respect to more discrete feature typeconcept relationships (e.g., fruit: visual-perceptual color, animal: visual-perceptual form) and across performance of persons with aphasia with different lesion profiles (e.g., Gainotti, 2006; see also Antonucci, 2014aAntonucci, , 2014b.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli were 36 concrete objects selected from a larger set of 60 (Antonucci, 2014b). To avoid fatigue effects, each participant responded to either set A or set B, each of which comprised half of the selected stimuli (i.e., nine living and nine nonliving).…”
Section: Experimental Verbal Description Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Antonucci (2014) demonstrated that some PWA have impaired access to certain types of knowledge more than others. Yet, all these studies used single concepts.…”
mentioning
confidence: 99%
“…This may present as a differential access to certain types of features (Antonucci, 2014; Marques, Mares, Martins, & Martins, 2013; Mason-Baughman & Wallace, 2014; Thompson & Jefferies, 2013). To date, researchers have not investigated whether modality-specific features differ in PWA and healthy controls, and while several researchers have examined how semantic feature based treatment influences discourse (Boyle, 2004; Peach & Reuter, 2010; Rider, Wright, Marshall, & Page, 2008), none have investigated how semantic knowledge types are used within discourse.…”
mentioning
confidence: 99%